Complete Genome Sequence of Pseudomonas aeruginosa FA-HZ1, an Efficient Dibenzofuran-Degrading Bacterium - Ali, Fawad (Genome Announc, 2017)
Pseudomonas sp. FA-HZ1, an efficient dibenzofuran-degrading bacterium, was isolated from landfill leachate. Here, we present the complete genome sequence of strain FA-HZ1, which contains only one circular chromosome. The complete genome sequence will be essential for revealing the molecular mechanisms of dibenzofuran degradation.